Our Intertwined Animality: Forgoing Ultimacy for Intimacy in Dialogue with Eschatology and Science - Harvie, Timothy (Studies in religion, 2020)
This article examines some epistemological issues arising in eschatology when read in dialogue with scientific projections for the cosmos. In noting the problematic of traditional Christian eschatologies, affirmations pertaining to human participation in transcendence, it is argued that exchanging notions of eternity for those of embodied, evolutionary relations is a productive avenue to pursue. In dialogue with Maurice Merleau-Ponty the article develops an eschatological conception of evolved animal flesh and its import for human relations with other species. The article concludes in proposing the concept of enactivism in constructing future eschatologies in dialogue with the natural sciences.